1998
DOI: 10.4052/tigg.10.235
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of .ALPHA.1-Acid Glycoprotein(Orosomucoid) in Health and Disease: Occurrence, Regulation and Possible Funtional Implications.

Abstract: ƒ¿1-Acid glycoprotein (AGP) is an acute-phase glycopro-tein with five .N linked glycans, exhibiting substantial heteroge-neity in their structures. This heterogeneity results from the presence in plasma of various distinct AGP glycoforms of which the plasma levels, and thus the relative occurrence of these glycoforms, are strictly dependent on the pathophysi-ological condition determined by cytokines and hormones. These humoral factors induce changes in the glycosylation process of the parenchymal liver cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 7 publications
2
30
1
1
Order By: Relevance
“…[43]). A masking effect of selectins was already proposed for the strongly fucosylated and sialyl Lewis X -containing AGP glycoform present in acute-phase plasma [12,13]. Indeed, studies in an ischemiareperfusion model in rats support this notion [14].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…[43]). A masking effect of selectins was already proposed for the strongly fucosylated and sialyl Lewis X -containing AGP glycoform present in acute-phase plasma [12,13]. Indeed, studies in an ischemiareperfusion model in rats support this notion [14].…”
Section: Discussionsupporting
confidence: 61%
“…A minor fraction of AGP was detected at 41-43 kD, the apparent molecular weight generally found for human plasma AGP (Fig. 1) [10,13]. Both AGP variants appeared to be present as soluble proteins in PMN, as they were recovered almost completely in the 100,000 g supernatant of cells that were lysed by repeated freezing and thawing (Fig.…”
Section: Characteristics Of Pmn Agpmentioning
confidence: 94%
See 1 more Smart Citation
“…Acute phase reaction may lead to other alterations than concentration changes in heavily glycosylated proteins such as AGP, for example changes in glycan composition as shown for AGP in other species [32,33]. To the best of our knowledge, only one paper is available reporting the differences in glycosylation patterns of boAGP from bovines of different ages [14] and this aspect should be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] The glycans of AGP are reported to influence its biological activities and to modulate cell-to-cell interactions and cellular signaling. 9,17 During the inflammatory process the sialylated and fucosylated glycotopes of AGP are reported to be involved in anti-inflammatory and immunomodulatory reactions. Van Dijk et al 17 have suggested that AGP molecules carrying sialyl-Lewis x glycotopes may interfere with leukocyteendothelial interactions by binding to E-or P-selectin and possess anti-inflammatory properties.…”
Section: Introductionmentioning
confidence: 99%